Learning that lasts: developing 4C skills in college English through Understanding by Design framework - Liu, Yuanbo; Khalid, Fariza; Nasri, Nurfaradilla Mohamad (Frontiers in Education, 2026)
In the context of rapid social development and ongoing national education modernisation, the English curriculum is expected to shift from traditional knowledge transmission to cultivating students’ core competencies, necessitating more effective pedagogical models. Grounded in the Understanding by Design (UbD) framework, this study examines how a UbD-based curriculum module (UbD module) can be applied to enhance college students’ 4C skills—creativity, critical thinking, communication, and collaboration. This study employs a quasi-experimental design, supplemented by semi-structured interviews. Quantitative data were collected from 119 college students via a questionnaire and analyzed using both independent-samples and paired-samples t-tests. Qualitative data were obtained through semi-structured interviews and analyzed using thematic analysis. The findings suggest that a UbD module is more effective than traditional methods in enhancing students’ creativity (p < 0.05, d = 0.52), critical thinking (p < 0.05, d = 0.26), and collaboration (p < 0.05, d = 0.36), while gains in communication were non-significant (p > 0.05). This study addresses the limited application of the UbD framework in Chinese college English education and offers an operational teaching paradigm English reform and 4C skills development.